PENGARUH PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA - Hotimah, Husnul (Faculty of Economic and Business, 2014)
Profit is an assertion of management that needs to be proven its quality. However, reported earnings do not necessarily reflect the real situation, because it allows the case of earnings management. There are various tools that can be done to explain earnings management, including in terms of tax planning. Thus, this study aims to examine the relationship between tax planning with earnings management. The study uses data companies listed on the Indonesian Stock Exchange in 2009 until 2011. Sample included 84 companies consisting of 49 companies in 2010 and 35 companies in 2011. Tax planning include the effective tax rate and deferred tax expense while earnings management is measured by the current discretionary accruals. The results of empirical testing using e-views 6 shows that positive tax planning proxy significantly related to earnings management is the effective tax rate. While the deferred tax expense not found a significant relationship. In general, the results showed that the tax planning has effect on the amount of current discretionary accruals.DOI: 10.15408/ess.v4i1.1963